The Pulse of Value: Early Warning Systems and Financial Health as Crucial Determinants for Sharia Insurance Firms - M Atoillah; Ulfi Kartika Oktaviana; Razali Ade Syahputra Hasibuan (Maliki Islamic Economics Journal, 2025)
This study aims to examine the effect of the Early Warning System (EWS), solvency, and profitability on the value of Islamic insurance companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. This study employs an associative quantitative method within a positivistic paradigm, using panel data from six companies, totalling 120 observations. The analysis was conducted using the Fixed-Effects Model (FEM) in EViews 12. The results show that liquidity, claim expenses, Risk-Based Capital (RBC), and Return on Assets (ROA) have a significant effect on company value, whereas changes in surplus do not. The simultaneous test (F-test) indicates that all variables collectively affect company value, with an Adjusted R² of 0.517. This study highlights that implementing an effective EWS is a strategic, prudential tool for improving transparency, risk management, and sharia-compliant financial sustainability.